IMPLEMENTASI CRM PENJUALAN JENIS PESTISIDA DAN BIBIT SAYURAN BERBASIS WEB - Gundari, Putri; Nurwati, Nurwati; Rahayu, Elly (STMIK Royal Kisaran, 2025)
Abstract: The development of Information and Communication Technology has transformed various aspects of life, including business. Amid increasing competition, maintaining customer loyalty has become a top priority. Customer Relationship Management (CRM) is a strategy that focuses on maintaining good relationships with customers. This study examines the implementation of CRM in the sales of pesticides and vegetable seeds at UD. Bersama, located in Punggulan Village, Asahan Regency. UD. Bersama faces challenges such as manual promotion, error-prone transaction recording, and limited customer reach. Product sales are unstable each month. To address these issues, a web-based sales system was designed at https://udbersamatani.online/, enabling online purchases, discounts, live chat, and free shipping services. The implementation results show that this system facilitates data processing and report generation for the admin. Consumers can quickly order products, interact via live chat, and obtain real-time product information. The application of CRM at UD. Together has proven effective in managing and analyzing data, meeting customer needs, and increasing sales. This system improves service and eases transactions for customers, potentially enhancing customer loyalty and satisfaction.Keywords: information technology; crm; pesticides; vegetable seeds; customer loyaltyAbstrak: Perkembangan Teknologi Informasi dan Komunikasi telah mengubah berbagai aspek kehidupan, termasuk bisnis. Di tengah persaingan yang semakin ketat, menjaga loyalitas pelanggan menjadi prioritas utama. Customer Relationship Management (CRM) adalah strategi yang fokus pada hubungan baik dengan pelanggan. Penelitian ini mengkaji implementasi CRM dalam penjualan pestisida dan bibit sayuran di UD. Bersama, Desa Punggulan, Kabupaten Asahan. UD. Bersama menghadapi kendala promosi manual, pencatatan transaksi yang rentan kesalahan, dan jangkauan pelanggan terbatas. Penjualan produk tidak stabil setiap bulan. Untuk mengatasi masalah ini, dirancang sistem penjualan berbasis web di https://udbersamatani.online/, yang memungkinkan pembelian online, diskon, live chat, dan layanan pengiriman gratis. Hasil implementasi menunjukkan sistem ini memudahkan admin dalam pengolahan data dan penyusunan laporan. Konsumen dapat memesan produk dengan cepat, berinteraksi melalui live chat, dan mendapatkan informasi produk secara real-time. Penerapan CRM di UD. Bersama terbukti efektif dalam mengelola dan menganalisis data, memenuhi kebutuhan pelanggan, serta meningkatkan penjualan. Sistem ini meningkatkan pelayanan dan mempermudah transaksi bagi pelanggan, sehingga berpotensi meningkatkan loyalitas dan kepuasan pelanggan.Kata kunci: teknologi informasi; crm; pestisida; bibit sayuran; loyalitas pelanggan